Right radical hemicolectomy secondary to cecal appendix mucocele: case report - Sánchez, Omar S.; Ramos, Monserrat A. V.; Pérez, Yoselin J. S.; Morales, Carlos P.; Barrientos, Cheryl Z. D.; Orea, Marco A. C. (International Journal of Research in Medical Sciences, 2023)
The cecal appendix mucocele is considered a cystic dilation of obstructive etiology that produces an accumulation of mucoid substance. It may be of benign or malignant origin. 50-year-old female, with no significant personal pathological history, presents with repetitive clinical symptoms of abdominal pain, similar to the process of acute appendicitis, without systemic inflammatory response data, which improves with analgesic management, is protocolized by laboratory studies and imaging, diagnosing appendicular tumor, so it is protocolized for surgical resolution, during which it is decided to do right hemicolectomy due to the macroscopic features of ascending colon. The clinical course and prognosis of mucinous appendicular lesions are closely related to their histology and the presence and extent of peritoneal dissemination. With a survival of 91 to 100% after a conventional appendectomy. The cecal appendix mucocele is considered a benign neoplasm; with good survival provided it is diagnosed in time and an appropriate surgical approach is performed; in our case fortunately it could be protocolized correctly; perform a surgical resection with free edges of oncological cells confirmed by histopathology, so our patient could be discharged from the service being free of oncological pathology at this time.